Construction of “enemy’s” image in soviet press in 1939-1953-s - Sirenko, Lidiia (Torun International Studies, 2015)
The article presents how in Soviet Union through children’s press government tried to raise new generation of Soviet men, who would be loyal to communists regime. As the main tool was used image of “enemy”, which consisted of two main parts: “external” and “internal enemies”. “Enemy’s” concept was not constant. The article examines evolution of the concept and its connection with the geopolitical situation and economic and political processes within the Soviet state. Children were taught how to identify “enemy” among other citizens, where they located, how they looks like, what values they have. And why it was so important for Soviet child to be attentive and report about all suspicious persons.